The Effect Of Organizational Culture And Leadership On The Performance Of Police Members - Pupung Pamungkas; Nining Kurniasih (SINTESA, 2022)
The core of the problem in this research is the Influence of Organizational Culture and Leadership on the Performance of Police Members (Perception Study of Satlantas at the Cianjur Police Resort). This study uses a survey approach, and part analysis. The data collection techniques used are observation, interviews, questionnaires, literature studies and documentation studies as well as data processing related to the problems studied, namely Organizational Culture and Leadership on the Performance of Satlantas Members at the Cianjur Police Resort. The analytical technique used is Part Analysis, Hypothesis Testing, Correlation Test, and Coefficient of Determination. The results of the discussion show that the Influence of Organizational Culture and Leadership on the Performance of Police Members (Perception Study of Traffic Traffic Units at the Cianjur Police Resort. It can be seen that the Influence of Organizational Culture and Leadership on the Performance of Traffic Police Members in Cianjur is 32.9% this figure shows a fairly strong correlation. This means that this figure shows that there is a fairly strong influence and there are 67.1% of other factors that affect the performance of members of the Cianjur Satlantas.The results of the test of the influence between Organizational Culture on Member Performance of (0.484)2 = 23.4% thus there is a significant at 0.000, meaning that there is an influence between variables Organizational Culture on Member Performance at the Cianjur Traffic Traffic Unit, and the results of the test of the influence between Leadership on Member Performance of (0.171)2 = 2.9%, thus there is no significant at 0.056, meaning that there is no influence between the Leadership variable on the Performance of the Cianjur Satlantas Members. Culture Organization and leadership have an influence on the performance of members of the Cianjur Satlantas can be accepted.